The significant relationship between independent and student’s motivation on online-based mathematics learning - Tetty Natalia Sipayung; Imelda Imelda; Tatag Yuli Eko Siswono; Masriyah Masriyah (Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
The purpose of this quantitative research with correlational design is to determine whether there is independent learning with learning motivation in online-based mathematics learning. So, it can support the success of learning process. This study was conducted in the odd semester of the 2021/2022 Academic Year. All seventh-grade students of SMP Santo Yoseph Medan were used as the research population. While the samples of this study were all students of class VII-A who collected 30 people and all students of class VII-B who collected 31 people. In mathematics learning, all students are taught online through the Zoom cloud meeting platform, WhatsApp, and Google Classroom. Sampling was done by purposive sampling technique. The study instruments is a learning independence questionnaire and student learning motivation questionnaire. The results of the questionnaire were analyzed based on product moment correlation data. Data analysis of the research results showed sig. (2-tailed) < 0.05 so that there is a significant relationship between learning independence and students' learning motivation in online-based mathematics learning with a value of 0.433 including the category of moderate correlation.